Entre palavra e imagem : Gémeos, de Mário Cláudio - Pavlichenko, Loiana Leal (2008)
The main objective of this work is to reflect about the critical dimension of Mário Cláudio s writing from the study of his novel, Gémeos. For such, some structural procedures will be taken into consideration, such as: the strategy of deception elaborated by means of the narrative voices and the composition of these, as well as the one of the characters, as a specular disposal through which also weaves the dialogue between the word and the image, or either, between Mário Cláudio s writing and Goya s painting. In the same way, it will be analyzed how some aesthetic procedures used by the author, such as the spalling, the citation, the perversion and the distortion of speeches are combined, thus the novel may be placed among the objects of art that are considered as neo-baroque. All the analysis will be developed in order to demonstrate that Gémeos discloses itself as a space where reflections about aesthetic activity are developed.